Assessment of Non-invasive Markers for the Prediction of Esophageal Variceal Hemorrhage - Li, Shasha; Huang, Peng; Jeyarajan, Andre J.; Ma, Chao; Zhu, Ke; Zhu, Chuanlong; Jiang, Ning; Li, Ming; Shao, Tuo; Han, Mingfeng; Tan, Lin; Lin, Wenyu (Frontiers in Medicine, 2021)
Background: Esophageal variceal (EV) hemorrhage is a life-threatening consequence of portal hypertension in cirrhotic patients. Screening upper endoscopy and endoscopic variceal ligation to identify and treat EVs have contraindications, complications, and high costs. We sought to identify noninvasive tests (NITs) as alternatives to endoscopic EV screening. Methods: In this case-control study, we retrospectively analyzed 286 cirrhotic patients treated for EVs at the Second People's Hospital of Fuyang City, China from January to December 2019. We applied ROC curve analysis to assess the accuracy of various NITs in predicting EV hemorrhage. Results: There were significant differences between the hemorrhage and non-hemorrhage groups in median serum albumin (ALB) (p<0.001), median bilirubin (TBIL) (p<0.046), prothrombin (PT) time (p<0.001), Golgi protein 73 (GP73; p=0.012) and Child-Pugh (C-P) scores (p<0.001). For ALB (cutoff < 33.2g/L), PT time (cutoff > 14.2 seconds), GP73 (cutoff > 126.4ng/ml), and C-P scores, the areas under the ROC curves (AUCs) were 73.4% (95% CI: 67.5-79.2), 68.6% (95% CI: 62.4-74.8), 62.2% (95% CI: 52.8-71.5) and 69.8% (95%CI: 63.8-75.8), respectively, with corresponding sensitives of 71.5%, 59.8%, 69.8%, and 92.2% and specificities of 65.6%, 70.1%, 56.5%, and 38.6%. When ALB was combined with GP73, the AUC was 74.3% (95% CI: 66.1-82.5) with a sensitivity of 65.1% and specificity of 76.5%. When ALB, PT, and C-P scores were combined, the AUC was 76.5% (95% CI: 70.9-82.1) with a sensitivity of 79.5% and specificity of 64.3%. When ALB, PT, GP73, and C-P scores were combined, the AUC was 75.2% (95% CI: 67.3-83.1) with a sensitivity of 54.0% and specificity of 86.9%. Conclusion: ALB, TBIL, GP73, and C-P scores, may be used to predict EV hemorrhage in cirrhotic patients. The combination of multiple NITs is better than a single index and can increase diagnostic performance.